Trapezoidal Scheme for the Numerical Solution of Fractional Initial Value Problems - Batiha, Iqbal M.; Alsamad, Hebah F.; Jebril, Iqbal H.; Al-Khawaldeh, Hamzah O.; Kasasbeh, Wala’a A. Al; Momani, Shaher (International Journal of Robotics and Control Systems, 2025)
The purpose of this study is to recall the main concepts and definitions in relation to the fractional calculus. In light of this overview, we will propose a novel fractional version of the so-called Trapezoid method named by the fractional Trapezoid method. Such a method will then be used to numerically solve the analog version of the initial value problems called fractional initial value problem FIVPs. As consequences of the proposed numerical approach, several numerical examples will be illustrated to verify the efficiency of the proposed numerical approach.